Beneficial effect of 8-ornithin vasopressin on renal dysfunction in decompensated cirrhosis. Issue 1 (January 1989) - Lenz, K; Hörtnagl, H; Druml, W; Grimm, G; Laggner, A; Schneeweisz, B; Kleinberger, G
Abstract : In nine patients with decompensated alcoholic cirrhosis of the liver and impaired renal function the effect of 8-ornithin vasopressin (ornipressin) on renal function and haemodynamic parameters was studied. Ornipressin was infused at a dose of 6 IU/h over a period of four hours. During ornipressin infusion an improvement of renal function was achieved as indicated by an increase of creatinine clearance (76 (15)%; p less than 0.01), urine volume (108 (29)%; p less than 0.05) and sodium excretion (168 (30)%; p less than 0.05). The hyperdynamic circulation of hepatic failure, as characterised by increased cardiac index and heart rate as well as decreased systemic vascular resistance was reversed to a nearly normal circulatory state during ornipressin infusion. The raised noradrenaline plasma concentration (1.74 (0.31) ng/ml) and plasma renin activity (13.5 (3.9) ng/ml/h) were lowered during ornipressin infusion to 0.87 (0.21) ng/ml and 5.9 (2.1) ng/ml/h, respectively (p less than 0.01). The efficacy of a vasoconstrictor agent in reverting a hyperdynamic state and improving renal function provides evidence for the substantial role of accumulation of vasodilator substances and subsequent activation of sympathetic nervous system and renin-angiotensin-axis in the pathogenesis of renal dysfunction in hepatic failure. Values are expressed as mean (SE).